Escolarização e oportunidade de trabalho: uma pequena reflexão sobre um equívoco comum - Castro, Matheus Fernandes de [UNESP] (2013)
This article intends to deal with an ordinary link it does on education and type of work what can be achieved. In two studies we conducted, one with the motorcyclists of Assis, in the state Sao Paulo - under the theoretical and methodological Psychodynamics of Work -, and another with the couriers in São Paulo - under a methodological framework ethnographic -, as we noted this relationship was used professionals to explain their connection and within these activities remain so poor and so dangerous for this group. This connection self cupabilization favors workers by their situation in the labor market and a difficult see no alternative to this reality. Intend to contribute to this discussion show a possible hypothesis as established this relationship (education / access to work) and show how the changes in the political context and economic environment and the world, contributed to the reduction of jobs, increasing the number precarious jobs and unemployment.